The book of (even more) awesome - Pasricha, Neil (New York G.P. Putnam's Sons, 2011)
"The second book of awesome things by internationally best-selling author Neil Pasricha"--
1
Keywords: Conduct of life -- Humor; HUMOR / Form / Essays; SELF-HELP / Personal Growth / Happiness